2002
DOI: 10.1073/pnas.192101699
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin mediates food-odor associative learning in the nematode Caenorhabditis elegans

Abstract: We demonstrate that Caenorhabditis elegans is able to form an association between the presence of the odorant benzaldehyde and the food content of its environment. When exposed to 100% benzaldehyde for 1 h in the absence of food the naive attractive response is reduced, and we have found that this olfactory adaptation is attenuated by the presence of food. Contrary to nonassociative (single stimulus) learning theory, this response is not a function of the total time of exposure to benzaldehyde but rather an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
168
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 25 publications
3
168
0
2
Order By: Relevance
“…[12,33,40,45]) and, furthermore, supported the hypothesis that such studies may tap into fundamental neurobiological alterations that underlie drug addictions [7,33,58,65]. It demonstrated that a psychostimulant drug of abuse could be rewarding to an animal that, unlike mammalian species, exhibits a relatively simple neuronal organization.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…[12,33,40,45]) and, furthermore, supported the hypothesis that such studies may tap into fundamental neurobiological alterations that underlie drug addictions [7,33,58,65]. It demonstrated that a psychostimulant drug of abuse could be rewarding to an animal that, unlike mammalian species, exhibits a relatively simple neuronal organization.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, had crayfish used such contrast features to distinguish between the two environments provided during the CPP experiments, the striped environment may have been perceived as relatively novel (compared to the uniform nature of the other environment in the aquarium or their home container). In this respect, novelty has been strongly implicated in the susceptibility of stimuli to conditioning phenomena [10,16,34,45]. Most importantly, however, the contextual dependence of psychostimulant reward in crayfish can be tested in future experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this role, exogenous serotonin inhibited habituation to benzaldehyde in the absence of food. Furthermore, the presence of food had no effect on the habituation of serotonin deficient mutants, cat-4 and tph-1 (Nuttley et al 2002). Following odorant habituation, expression of the learned behavior can be modulated by contextual cues present during conditioning.…”
Section: Effect Of Context On Chemosensory Habituationmentioning
confidence: 93%
“…Nuttley et al (2002) showed that habituation to benzaldehyde was inhibited in the presence of food. This suggests a learned association, making worms less likely to ignore benzaldehyde if it is predictive of food.…”
Section: Effect Of Context On Chemosensory Habituationmentioning
confidence: 99%